Innovation and Communication: Signalling with Partial Disclosure - Bhattacharya, Sudipto; Ritter, Jay R. (Review of Economic Studies, 1983)
This paper introduces a model of “feedback effect equilibrium” i.e. equilibria in which an asymmetrically informed agent is motivated to communicate its privately known attribute but can do so only through channels or signals which convey directly useful information to competing agents. This revelation to the competition serves to reduce the value of the private information held by the first agent. Models of this kind are of obvious relevance to realistic theories of product or financial market disclosure policies of firms, patenting, and a host of related behavioural and regulatory issues. This model is developed in the context of a set of firms engaged in research and development rivalry, in which the value of privately held and disclosed information arises from its implications for the likelihood and timing of productive innovation.